Determinant of Post COVID-19 Vaccination (Sinovac) Adverse Events Among Health Care Workers in Palembang - Mustika Fatimah; Dianita Ekawati; Rico Januar Sitorus; Supli Effendi Rahim; Alfredo Armando Parensyah (Jurnal Ilmu Kesehatan Masyarakat, 2022)
The COVID-19 cases in Palembang are still increasing every day. This pandemic has forced the adaptation of the "New Normal" lifestyle, which will have an impact on communicable and non-communicable diseases. The Sinovac vaccine used in the COVID-19 vaccination program for Health Care Workers (HCW), which is a top priority, is still a new vaccine, so a survey of complaints and the determinant is important. This study aimed to survey complaints and the determinant of Post COVID-19 Vaccination (Sinovac) Adverse Events among HCW. A cross-sectional study was conducted in Palembang between June and August 2021 on 414 HCWs who received the COVID-19 vaccine injection. The instrument consisted of demographic characteristics, marital status, distance to health care facilities, Body Mass Index (BMI), diet, sleep quality, anxiety, and some medical histories. Overall, although many, all complaints were classified as mild. There was a significant relationship between age, anxiety, and history of food allergy with Post COVID-19 Vaccination Adverse Events (p-value = 0.003; 0.017; 0.050), and anxiety was the determinant of the adverse events (p-value < 0.05). However, there was a significant relationship between age, anxiety, and history of food allergy with Post COVID-19 Vaccination Adverse Events indicates that these factors need to be considered in determining the standard operational procedure for the next vaccination. While there was no significant relationship between obesity, diet, sleep quality, history of drug allergy, atopic disease, hypertension, and dyspepsia syndrome are expected to increase public knowledge and confidence so there will be no worries about receiving the vaccine.